The pedicled anterolateral thigh flap for trochanteric pressure sore reconstruction: Technical notes to optimize surgical outcomes - Mahmoud A. Hifny (Archives of Plastic Surgery, 2021)
Background The pedicled anterolateral thigh (ALT) flap has become more popular for the reconstruction of soft-tissue defects in neighboring areas. Nonetheless, few studies in the literature have explored the use of this flap for trochanteric ulcer reconstruction. The aim of our study is to present the author’s experience of utilizing the ALT flap, with a focus on technical elements regarding the flap design and the tunneling method to maximize the reach of the flap. Methods The medical records of patients who received pedicled ALT flaps for the reconstruction of trochanteric pressure sores were retrospectively reviewed. The patients’ demographic data, operative details, and postoperative complications were evaluated. Results Between October 2018 and December 2019, 10 consecutive patients (age range, 13–45 years) underwent 11 pedicled ALT myocutaneous flaps for trochanteric pressure sore reconstruction. Each flap was designed around the most distal cutaneous perforator that was included in the proximal third of the skin paddle. The flaps ranged in size from 11×6 to 14×8 cm. The ALT flap was transposed through a lateral subcutaneous tunnel in five patients, while the open tunnel technique was used in six patients. All flaps survived, and no vascular compromise was observed. Conclusions The pedicled ALT flap is a safe and reliable option for reconstructing trochanteric pressure sores. An appropriate flap design and a good choice of the tunneling method are crucial for successful flap transposition.